Key antecedents influencing customer satisfaction with service recovery: a case of airlines in Malaysia / Nurliyana Abas - Abas, Nurliyana (2014)
The purpose of this study is to study the customer satisfaction with service recovery (CSSR) by examining the key antecedent dimensions that able to influence the satisfaction. Quantitative approach questionnaire was used for data collection. A total of 382 questionnaires were gathered from those who had experienced service failures with airlines in Malaysia namely MAS, Air Asia and Firefly. Findings indicate that key antecedents such as perceived justice (distributive, procedural, interactional), service recovery expectation, disconfirmation and empowerment significantly related in influencing CSSR. Empowerment become the most stringent factor that influence CSSR and generally, customer satisfaction level with recovery effort done by airlines in Malaysia is moderate. Furthermore, this study provide the contribution to body of knowledge by testing new dimensions such as service recovery expectation and empowerment in one single model. This study also offers important implications, limitations and further directions for future research.